2021
DOI: 10.1007/s00268-021-06098-0
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Imaging in Renal Transplant Patients with Tertiary Hyperparathyroidism

Abstract: Background Tertiary hyperparathyroidism following kidney transplantation is most commonly characterized by 4‐gland hyperplasia, but single and double adenomatous disease has been demonstrated in this population as well. It is unknown whether preoperative imaging can assist in identifying patients who may qualify for focused surgery for adenomatous disease. Materials and methods We performed a retrospective review of our patient database from 1998–2018 for patients with tertiary hyperparathyroidism following re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Ultrasonography is easy to perform but has poor sensitivity. 99mTc-MIBI single-photon emission computed tomography associated with computed tomography scintigraphy (SPECT/CT) improves the sensitivity of preoperative parathyroid localization and accurately locates ectopic parathyroid glands ( 6 ). As a result, for refractory SHPT, ultrasound combined with SPECT/CT is the best choice for preoperative localization ( 48 ), while CT and MIBI scans are effective imaging modalities for the assessment of postoperative residual parathyroid glands and prior to repeat PTX ( 49 ).…”
Section: Treatment For Hptmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasonography is easy to perform but has poor sensitivity. 99mTc-MIBI single-photon emission computed tomography associated with computed tomography scintigraphy (SPECT/CT) improves the sensitivity of preoperative parathyroid localization and accurately locates ectopic parathyroid glands ( 6 ). As a result, for refractory SHPT, ultrasound combined with SPECT/CT is the best choice for preoperative localization ( 48 ), while CT and MIBI scans are effective imaging modalities for the assessment of postoperative residual parathyroid glands and prior to repeat PTX ( 49 ).…”
Section: Treatment For Hptmentioning
confidence: 99%
“…In tertiary hyperparathyroidism (THPT), long-term overstimulation of the parathyroids leads to the development of nodules due to the compensatory hyperfunction to spontaneous PTH incretion. THPT is common in patients with long-term chronic kidney disease, hemodialysis, and kidney transplantation ( 6 ). HPT can cause bone diseases ( 7 ), such as pathological fractures or skeletal deformities, cardiovascular diseases ( 8 ), and kidney stones and may also induce end-stage parathyroid cancer, although this is extremely rare ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that preoperative planning with nuclear imaging reduces the extent of surgical resection as well as the rate of surgical failure due to missing ectopic parathyroid glands [ 4 , 5 ]. If in our case poor medical drug response should be noted, the three most hyperactive parathyroid glands would be selectively removed by the surgeon based on the choline PET imaging findings [ 6 , 7 ]. Imaging directed based surgery reduces redo-surgeries and the perioperative complication rate will be very low [ 6 ].…”
mentioning
confidence: 99%